2010
DOI: 10.1063/1.3332585
|View full text |Cite
|
Sign up to set email alerts
|

Protein elasticity probed with two synchrotron-based techniques

Abstract: Compressibility characterizes three interconnecting properties of a protein: dynamics, structure, and function. The compressibility values for the electron-carrying protein cytochrome c and for other proteins, as well, available in the literature vary considerably. Here, we apply two synchrotron-based techniques--nuclear resonance vibrational spectroscopy and inelastic x-ray scattering--to measure the adiabatic compressibility of this protein. This is the first report of the compressibility of any material mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 90 publications
2
36
0
Order By: Relevance
“…The structure changes associated with cyt c binding to model membrane systems (polyanions 75 , phospholipid vesicles 76 and electrodes 77 ) as well as intact mitochondria 78 has also been investigated. The studies of model membrane systems demonstrated that cyt c undergoes a tertiary structural change upon binding.…”
Section: Discussionmentioning
confidence: 99%
“…The structure changes associated with cyt c binding to model membrane systems (polyanions 75 , phospholipid vesicles 76 and electrodes 77 ) as well as intact mitochondria 78 has also been investigated. The studies of model membrane systems demonstrated that cyt c undergoes a tertiary structural change upon binding.…”
Section: Discussionmentioning
confidence: 99%
“…Trp 59 is only a single Tryptophan (Trp) residue located at 9 Å from the heme and its emission is highly sensitive to protein conformations and quenched by fluorescence resonance energy transfer to the heme group ,. The dynamics of different intermediates and conformational changes of the folded and unfolded forms of Cyt c under various conditions were studied extensively by using different spectroscopic techniques including absorption, electronic and magnetic circular dichroism, nuclear magnetic resonance, electron paramagnetic resonance, X‐ray diffraction, inelastic X‐ray scattering, and resonance Raman spectroscopy…”
Section: Introductionmentioning
confidence: 99%
“…As ignificant shortening of the excited-state lifetime of Trpi so bserved at various pH values at 280 nm excitation due to resonance energy transfer to the heme. The longer time constant (25 ps) observed in the unfoldedf orm is attributed to ac omplete global conformationalrelaxation of Cyt c. cular dichroism, [10] nuclear magnetic resonance, [11] electron paramagnetic resonance, [12] X-ray diffraction, [7,13] inelastic X-ray scattering, [14] andr esonance Ramanspectroscopy. [15] The ultrafast dynamics of the heme in ferric Cytchave been widely investigated by using femtosecond pump-probe spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“… 19 , 20 , 21 , 22 , 28 GFP has a remarkable regular structure that is stable and resistant to unfolding so that even the water molecules on the outside of the barrel form “stripes.” 29 Therefore, GFP is a suitable model system for INS measurements. In our experiment, we observed propagating acoustic 21 , 23 , 28 , 30 , 31 and non-propagating localized 19 , 20 , 21 , 22 modes from both samples. Further analysis of such excitations helped us to understand the relations between protein flexibility/softness and its activity from a physical perspective.…”
Section: Introductionmentioning
confidence: 54%
“…Phonon-like collective excitations in proteins have been investigated using inelastic X-ray scattering (IXS). 19 , 20 , 21 , 22 , 23 However, IXS has a limited energy resolution, especially for studying low-frequency collective excitations. 24 Compared with IXS, coherent inelastic neutron scattering (INS) technique is exceptionally suitable for investigating low-frequency collective excitations 24 , 25 and has been applied successfully to study collective density fluctuations in amorphous materials, glasses, or liquids.…”
Section: Introductionmentioning
confidence: 99%